Preparation method of polyimide fluorinated graphene composite film with bidirectionally adjustable dielectric constant

Fluorinated graphene/polyimide composite films were prepared by ultrasonic-assisted solvothermal intercalation and in-situ polymerization, solving the problem of unidirectional control of dielectric constant and realizing bidirectional control of dielectric constant in the range of 3.0-5.9, thereby improving the electrical, thermal and mechanical properties of power electronic devices.

CN120842631APending Publication Date: 2025-10-28SHANDONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510978267.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing polyimide composite films have a unidirectional dielectric constant control, making it difficult to achieve bidirectional control while maintaining the overall stability of the matrix material. This leads to a mismatch in the dielectric constants of multilayer insulating materials, affecting the operational stability of power electronic equipment.

Method used

Fluorinated graphene was exfoliated using an ultrasound-assisted solvothermal intercalation method and then polymerized in situ with polyamic acid to prepare fluorinated graphene/polyimide composite films with different fluorine-to-carbon ratios. The dielectric constant was controlled by the fluorine-to-carbon ratio of the fluorinated graphene, and fluorinated graphene with an extremely low doping amount of 0.5 wt% was fixed as the reinforcement.

Benefits of technology

The dielectric constant of polyimide/fluorinated graphene composite films can be bidirectionally tuned within the range of 3.0-5.9, improving electrical, thermal, and mechanical properties. The thermal conductivity and electrical insulation properties are significantly enhanced, making them suitable for packaging high-frequency power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842631A_ABST
    Figure CN120842631A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyimide fluorinated graphene composite film with a bidirectionally regulated dielectric constant, relates to the technical field of new materials, and is used for solving the problem that the dielectric constant of the existing polyimide fluorinated graphene composite film cannot be bidirectionally regulated. Comprising the following steps: S1, stripping graphite fluoride into fluorinated graphene in an N-methyl-2-pyrrolidone solution through an ultrasonic-assisted solvothermal intercalation method, then carrying out low-speed centrifugation on a dispersion liquid once to obtain an upper-layer dispersion liquid, and then carrying out high-speed centrifugation once to obtain a precipitate solution, and carrying out suction filtration, washing, drying and grinding on the precipitate solution to obtain fluorinated graphene powder. And S2, preparing a composite solution of fluorinated graphene and polyamide acid with different fluorocarbon ratios through an in-situ polymerization method, coating the composite solution on a clean glass plate by adopting a solution tape casting method, and carrying out defoaming and thermal imidization reaction to obtain the polyimide fluorinated graphene composite film. According to the invention, the fluorinated graphene composite film with bidirectionally regulated dielectric constant can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials technology, specifically a method for preparing polyimide fluorinated graphene composite films with bidirectionally tunable dielectric constant. Background Technology

[0002] With the increasing demand for new energy power generation and ultra-high voltage power transmission, high-frequency power electronic equipment in DC power transmission is developing towards larger capacity, higher voltage, higher power density, and smaller, lighter designs. These new equipment characteristics, resulting in high power density and high-frequency electrical stress, place new demands on the insulation of power electronic equipment. Multilayer composite insulation structures are a key means to achieve equipment insulation goals, such as the polyimide and epoxy resin composite insulation system in high-frequency transformers, the polyimide and silicone gel composite insulation system in IGBT power modules, and the polyimide and mica composite insulation system in motor insulation. Composite insulation structures provide electrical insulation strength and mechanical support strength for the equipment; however, the difference in dielectric constant among the multilayer insulation materials makes it easy for high-frequency electrical stress to generate continuous partial discharge and spatial electric field distortion, seriously affecting the operational stability of power electronic equipment.

[0003] Polyimide is formed by the condensation polymerization of aromatic dianhydrides and diamines to create a rigid aromatic heterocyclic structure. The imide bonds in the main chain endow it with excellent properties: good thermal stability, electrical insulation, mechanical properties, and chemical resistance. These advantages make polyimide a common choice for interlayer insulation materials in power electronic devices and it is widely used in electrical engineering and microelectronics. However, the dielectric constant of pure polyimide is around 3.5, which differs from that of cast insulating materials such as epoxy resin, silicone gel, and mica, easily leading to severe electric field distortion and insulation failure risks. Current methods can only unidirectionally change the dielectric constant of polyimide-based composites; in practical applications, different methods must be used to match the dielectric constant.

[0004] Chinese patent CN116285347B discloses a high thermal conductivity, low dielectric constant polyimide film. The dielectric constant of the composite film is gradually reduced by increasing the proportion of porous boron nitride filler. Chinese patent CN117487352A discloses a low dielectric constant porous polyimide microsphere / polyimide composite film, its preparation method, and its applications. Porous polyimide microspheres with a particle size of 1-3 micrometers are used as filler; the dielectric constant of the composite film gradually decreases as the filler content gradually increases. Chinese patent CN111925540B discloses a high dielectric constant nano-perovskite CsPbX3 / polyimide composite film and its preparation method. Different proportions of perovskite filler are doped into the polyimide matrix to obtain the high dielectric constant composite film. Chinese patent CN119505308A discloses a high-entropy ceramic-polymer composite energy storage dielectric film. By increasing the proportion of high-entropy ceramic in the "core-shell" structure, the dielectric constant of the polymer film is gradually increased.

[0005] While the existing technologies described above achieve the goal of reducing or increasing the dielectric constant of polyimide composite films by increasing the filler content, the change in dielectric constant is unidirectional. To achieve dielectric constant matching in multilayer composite insulation materials, porous fillers need to be introduced into the insulation portions with higher dielectric constants to reduce them, while polar fillers need to be introduced into the insulation portions with lower dielectric constants to increase them. This can easily lead to difficulties in matching other physicochemical properties among the multilayer insulation materials. Therefore, there is an urgent need for a strategy that can bidirectionally control the dielectric constant while maintaining the overall stability of the matrix material. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing polyimide fluorinated graphene composite films with bidirectionally adjustable dielectric constant, thereby solving the problem that the dielectric constant of existing polyimide fluorinated graphene composite films cannot be bidirectionally adjusted.

[0007] The technical solution adopted by this invention to solve its technical problem is: a method for preparing a polyimide fluorinated graphene composite film with bidirectionally adjustable dielectric constant, comprising the following steps: S1. Fluorinated graphite is exfoliated into fluorinated graphene in N-methyl-2-pyrrolidone solution by ultrasonic-assisted solvothermal intercalation. The dispersion is then centrifuged once at low speed to obtain the upper dispersion, and then centrifuged once at high speed to obtain the precipitate solution. The precipitate solution is filtered, washed, dried and ground to obtain fluorinated graphene powder.

[0008] S2. Composite solutions of fluorinated graphene and polyamic acid with different fluorine-to-carbon ratios were prepared by in-situ polymerization. The composite solutions were coated on a clean glass plate by solution casting and subjected to defoaming and thermal imidization reactions to obtain polyimide fluorinated graphene composite films.

[0009] Furthermore, to ensure the overall stability of the electrical, thermal, and mechanical properties of the composite film, the preferred mass fraction of fluorinated graphene is 0.5 wt%.

[0010] Furthermore, in order to obtain fluorinated graphene with different fluorine-to-carbon ratios, the fluorine-to-carbon ratio of the fluorinated graphene was controlled by ultrasound, and the ultrasound time of the fluorinated graphene composite solution was 4-128 h.

[0011] Furthermore, to obtain fluorinated graphene with a fluorine-to-carbon ratio of 1, the ultrasonic time is preferably 3-6 hours.

[0012] Furthermore, to obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.9, the ultrasonic time is preferably 12-18 hours.

[0013] Furthermore, to obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.7, the ultrasonic time is preferably 28-36 hours.

[0014] Furthermore, to obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.6, the ultrasonic time is preferably 100-140 h.

[0015] Furthermore, during the low-speed centrifugation of the fluorinated graphene dispersion, the rotation speed was 800-2000 rpm and the centrifugation time was 8-15 min.

[0016] Furthermore, during the low-speed centrifugation of the fluorinated graphene dispersion, the rotation speed was 1000-1500 rpm and the centrifugation time was 10-12 min.

[0017] Furthermore, during the high-speed centrifugation of the fluorinated graphene dispersion, the rotation speed was 6000-10000 rpm and the centrifugation time was 8-15 min.

[0018] Furthermore, the fluorinated graphene dispersion was centrifuged at a speed of 7000-8000 rpm for 10-12 min.

[0019] The beneficial effects of this invention are: (1) Traditional methods for adjusting the dielectric constant of insulating materials often require increasing the filler content to decrease or increase the dielectric constant, or introducing different fillers to increase the dielectric constant. This invention uses polyimide as the matrix and fluorinated graphene as the reinforcement. By fixing the extremely low doping amount of 0.5 wt% fluorinated graphene, the dielectric constant of the polyimide / fluorinated graphene composite film prepared by changing the fluorine-carbon ratio of the fluorinated graphene can remain stable with frequency changes and can be controlled within the range of 3.0-5.9, overcoming the deficiency that the dielectric constant of traditional polyimide-based composite films can only be controlled unidirectionally.

[0020] (2) The polyimide / fluorinated graphene composite film prepared by the present invention maintains stable or even improves electrical, thermal, and mechanical properties while achieving bidirectional control of dielectric constant. The thermal conductivity of the composite film remains above 0.2 W / (m∙K), which significantly improves thermal conductivity and thermal stability compared to pure polyimide film (0.12 W / (m∙K)). The tensile strength of the composite film is above 100 MPa, which is higher than 67 MPa of pure polyimide film, and the tensile properties remain stable. The electrical insulation properties of the composite film increase with decreasing fluorine-carbon ratio of fluorinated graphene, with a minimum of 371.5 kV / mm and a maximum of 540.6 kV / mm, which is much higher than 301.6 kV / mm of pure polyimide film.

[0021] (3) This invention introduces fluorinated graphene into a polyimide matrix via in-situ polymerization. Benefiting from the large-diameter structure and high surface energy of fluorinated graphene, air micropores are successfully introduced into the polyimide / fluorinated graphene composite film. The size of the air micropores in the composite film decreases as the fluorine-carbon ratio of the fluorinated graphene decreases. Due to the low dielectric constant of air, the dielectric constant of the polyimide / perfluorinated graphene composite film is as low as 3.0, which can be applied to the packaging of high-frequency power electronic devices.

[0022] (4) The preparation method of the present invention is safe, easy to operate, uses safe and readily available materials, has good reproducibility and can be prepared on a large scale. The overall size of the composite film prepared by the present invention is controllable. The thickness of the polyimide / fluorinated graphene composite film can be adjusted by changing the coating thickness of the polyamic acid / fluorinated graphene composite solution. Attached Figure Description

[0023] Figure 1 The preparation process of fluorinated graphene with different fluorine-to-carbon ratios according to the present invention; Figure 2 The preparation process of the polyimide / fluorinated graphene composite film with bidirectionally tunable dielectric constant is described in this invention. Figure 3 These are cross-sectional microstructure images of pure polyimide films and polyimide / fluorinated graphene composite films prepared according to four embodiments of the present invention. Figure 4 The dielectric constant of pure polyimide films and polyimide / fluorinated graphene composite films prepared according to four embodiments of the present invention varies with frequency. Figure 5 The breakdown field strength distribution of pure polyimide films and polyimide / fluorinated graphene composite films prepared in four embodiments of the present invention; Figure 6 The thermal conductivity of pure polyimide films and polyimide / fluorinated graphene composite films prepared according to four embodiments of the present invention; Figure 7Thermogravimetric curves of pure polyimide films and polyimide / fluorinated graphene composite films prepared according to four embodiments of the present invention; Figure 8 Stress-strain curves of pure polyimide films and polyimide / fluorinated graphene composite films prepared according to four embodiments of the present invention. Detailed Implementation

[0024] In order to achieve a uniform electric field distribution in a multilayer composite insulation structure, it is particularly important to develop a polyimide-based composite film with bidirectionally adjustable dielectric constant while maintaining the overall stability of the electrical, thermal, and mechanical properties of the insulation material. This invention proposes a method for preparing a polyimide-fluorinated graphene composite film with bidirectionally adjustable dielectric constant.

[0025] This invention first prepares a pure polyimide film using a two-step method as a control to ensure that the electrical, thermal, and mechanical properties of the composite film proposed in this invention remain stable, except for the dielectric constant.

[0026] The preparation process of pure polyimide film includes the following steps: like Figure 1 As shown, (1) the diamine is dissolved in N,N-dimethylacetamide solution. After the diamine is completely dissolved, an equimolar amount of dianhydride is added to the mixed solution in three portions to obtain a polyamic acid solution. The diamine is preferably 4,4-diaminodiphenyl ether, and the dianhydride is preferably pyromellitic dianhydride. The dianhydride is added in batches to prevent excessive polymerization caused by adding too much at once. The number of additions is 1-10 times, preferably 2-5 times. The reaction conditions between the dianhydride and the diamine are 0-8 °C for 1.5-4 h, preferably 4-6 °C for 2-3 h.

[0027] (2) The solution was degassed under vacuum to remove air bubbles, and the polyamic acid solution was coated onto a clean glass plate using a casting method. Then, a thermal imidization reaction was carried out. After completion, the glass plate was cooled to room temperature, and the polyimide film was peeled off the glass plate in cold water. The thermal imidization reaction adopted a gradient heating method, and the preferred heating program was heating at 60°C for 2 hours, at 120°C for 30 minutes, at 200°C for 30 minutes, at 250°C for 30 minutes, and at 300°C for 30 minutes.

[0028] II. Figure 2 As shown, the preparation process of a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to the present invention includes the following steps: S1. Fluorinated graphite is exfoliated into fluorinated graphene in an N-methyl-2-pyrrolidone solution using an ultrasound-assisted solvothermal intercalation method. The dispersion is then subjected to a low-speed centrifugation to obtain the supernatant dispersion, followed by a high-speed centrifugation to obtain the precipitate solution. The precipitate solution is then filtered, washed, dried, and ground to obtain fluorinated graphene powder. Fluorinated graphene with different fluorine-to-carbon ratios is obtained by varying the ultrasonic treatment time.

[0029] To ensure the overall stability of the electrical, thermal, and mechanical properties of the composite film, the preferred mass fraction of fluorinated graphene is 0.5 wt%.

[0030] To obtain fluorinated graphene with different fluorine-to-carbon ratios, the fluorine-to-carbon ratio of the fluorinated graphene was controlled by ultrasound. The ultrasound time for the fluorinated graphene composite solution was 4-128 h. To obtain fluorinated graphene with a fluorine-to-carbon ratio of 1, the ultrasound time was preferably 3-6 h. To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.9, the ultrasound time was preferably 12-18 h. To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.7, the ultrasound time was preferably 28-36 h. To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.6, the ultrasound time was preferably 100-140 h.

[0031] During low-speed centrifugation of the fluorinated graphene dispersion, the rotation speed is 800-2000 rpm and the centrifugation time is 8-15 min, with the preferred rotation speed being 1000-1500 rpm and the preferred centrifugation time being 10-12 min; during high-speed centrifugation, the rotation speed is 6000-10000 rpm and the centrifugation time is 8-15 min, with the preferred rotation speed being 7000-8000 rpm and the preferred centrifugation time being 10-12 min.

[0032] S2. Composite solutions of fluorinated graphene and polyamic acid with different fluorine-to-carbon ratios were prepared by in-situ polymerization. The composite solutions were coated on a clean glass plate by solution casting and subjected to defoaming and thermal imidization reactions to obtain polyimide fluorinated graphene composite films.

[0033] III. The following describes the preparation process of a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant, based on specific examples.

[0034] Example 1 S1. 1 g of fluorinated graphene was dispersed in 200 mL of N-methyl-2-pyrrolidone, and the mixture was heated under reflux at 80°C for 2.5 h. After cooling to room temperature, the mixture was sonicated for 4 hours to obtain a mixed solution of fluorinated graphene and N-methyl-2-pyrrolidone. The resulting dispersion was then centrifuged at 1000 rpm for 10 min to obtain the upper dispersion to remove unintercalated fluorinated graphene. The upper dispersion was centrifuged at 8000 rpm for 10 min to obtain the lower layer containing precipitate. The precipitate was obtained by vacuum filtration, washed three times with deionized water, and then vacuum dried at 50°C for 24 h. The dried solid was ground to obtain fluorinated graphene powder. The atomic ratio of fluorine to carbon in the sample was determined by X-ray energy dispersive spectroscopy to be 0.96, and the sample was designated as FG-0.96.

[0035] S2. Polyimide / fluorinated graphene composite films were prepared by in-situ polymerization. First, 0.028 g of FG-0.96 was added to 35 ml of N,N-dimethylacetamide solution and sonicated for 5 minutes. Then, 3.065 g of 4,4-diaminodiphenyl ether was added to the mixture, and the composite solution was heated and stirred in a 40°C constant temperature water bath for 1 hour at a speed of 200 r / min. After the 4,4-diaminodiphenyl ether was completely dissolved, the water bath temperature of the composite solution was adjusted to 4℃. Then, 3.348g of pyromellitic dianhydride was added to the composite solution in three portions: 2g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 1.011g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; finally, 0.337g of pyromellitic dianhydride was added and stirred for 30 minutes, with the stirring speed adjusted to 100 rpm to reduce bubble formation. The composite solution was stirred for 35 minutes to ensure complete reaction. Stirring was stopped after the "climbing rod" phenomenon occurred, yielding a polyamic acid / FG-0.96 composite solution. The solution was then degassed under vacuum to remove bubbles, and the polyamic acid / FG-0.96 composite solution was coated onto a clean glass plate using a solution casting method. The glass plate was placed in a vacuum drying oven at 60°C for 2 hours, and then subjected to a gradient heating process: heating at 120°C for 30 min, 200°C for 30 min, 250°C for 30 min, and 300°C for 30 min. After the glass plate cooled to room temperature, the polyimide / FG-0.96 composite film was peeled off the glass plate in cold water.

[0036] Example 2 S1. 1 g of fluorinated graphene was dispersed in 200 mL of N-methyl-2-pyrrolidone, and the mixture was heated under reflux at 80°C for 2.5 h. After cooling to room temperature, the mixture was sonicated for 16 hours to obtain a mixed solution of fluorinated graphene and N-methyl-2-pyrrolidone. The resulting dispersion was then centrifuged at 1000 rpm for 10 min to obtain the upper dispersion to remove unintercalated fluorinated graphene. The upper dispersion was centrifuged at 8000 rpm for 10 min to obtain the lower layer containing precipitate. The precipitate was obtained by vacuum filtration, washed three times with deionized water, and then vacuum dried at 50°C for 24 h. The dried solid was ground to obtain fluorinated graphene powder. The atomic ratio of fluorine to carbon in the sample was determined by X-ray energy dispersive spectroscopy to be 0.88, and the sample was designated as FG-0.88.

[0037] S2. Polyimide / fluorinated graphene composite films were prepared by in-situ polymerization. First, 0.028 g of FG-0.88 was added to 35 ml of N,N-dimethylacetamide solution and sonicated for 5 minutes. Then, 3.065 g of 4,4-diaminodiphenyl ether was added to the mixture, and the composite solution was heated and stirred in a 40°C constant temperature water bath for 1 hour at a speed of 200 r / min. After the 4,4-diaminodiphenyl ether was completely dissolved, the water bath temperature of the composite solution was adjusted to 4℃. Then, 3.348g of pyromellitic dianhydride was added to the composite solution in three portions: 2g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 1.011g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 0.337g of pyromellitic dianhydride was added and stirred for 30 minutes, adjusting the stirring speed to 100 rpm to reduce bubble formation. The composite solution was stirred for 30 minutes to ensure sufficient reaction. Then, 0.03g of pyromellitic dianhydride was added and stirred for 30 minutes at 100 rpm. Stirring was stopped after the solution exhibited a "climbing" phenomenon, yielding the polyamic acid / FG-0.88 composite solution. The solution was then degassed under vacuum to remove air bubbles, and the polyamic acid / FG-0.88 composite solution was coated onto a clean glass plate using a solution casting method. The glass plate was placed in a vacuum drying oven at 60°C for 2 hours, followed by a gradient heating process: 120°C for 30 min, 200°C for 30 min, 250°C for 30 min, and 300°C for 30 min. After the glass plate cooled to room temperature, the polyimide / FG-0.88 composite film was peeled off from the glass plate in cold water.

[0038] Example 3 S1. 1 g of fluorinated graphene was dispersed in 200 mL of N-methyl-2-pyrrolidone, and the mixture was heated under reflux at 80°C for 2.5 h. After cooling to room temperature, the mixture was sonicated for 64 hours to obtain a mixed solution of fluorinated graphene and N-methyl-2-pyrrolidone. The resulting dispersion was then centrifuged at 1000 rpm for 10 min to obtain the upper dispersion to remove unintercalated fluorinated graphene. The upper dispersion was centrifuged at 8000 rpm for 10 min to obtain the lower layer containing precipitate. The precipitate was obtained by vacuum filtration, washed three times with deionized water, and then vacuum dried at 50°C for 24 h. The dried solid was ground to obtain fluorinated graphene powder. The atomic ratio of fluorine to carbon in the sample was determined by X-ray energy dispersive spectroscopy to be 0.68, and the sample was designated as FG-0.68.

[0039] S2. Polyimide / fluorinated graphene composite films were prepared by in-situ polymerization. First, 0.028 g of FG-0.68 was added to 35 ml of N,N-dimethylacetamide solution and sonicated for 5 minutes. Then, 3.065 g of 4,4-diaminodiphenyl ether was added to the mixture, and the composite solution was heated and stirred in a 40°C constant temperature water bath for 1 hour at a speed of 200 r / min. After 4,4-diaminodiphenyl ether was completely dissolved, the water bath temperature of the composite solution was adjusted to 4℃. Then, 3.348g of pyromellitic dianhydride was added to the composite solution in three portions: 2g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 1.011g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 0.337g of pyromellitic dianhydride was added and stirred for 30 minutes, adjusting the stirring speed to 100 rpm to reduce bubble formation. The composite solution was stirred for 30 minutes to ensure sufficient reaction. Then, 0.03g of pyromellitic dianhydride was added and stirred for 1 hour at 100 rpm. Stirring was stopped after the solution exhibited a "climbing" phenomenon, yielding the polyamic acid / FG-0.68 composite solution. The solution was then degassed under vacuum to remove air bubbles, and the polyamic acid / FG-0.68 composite solution was coated onto a clean glass plate using a solution casting method. The glass plate was placed in a vacuum drying oven at 60°C for 2 hours, followed by a gradient heating process: 120°C for 30 min, 200°C for 30 min, 250°C for 30 min, and 300°C for 30 min. After the glass plate cooled to room temperature, the polyimide / FG-0.68 composite film was peeled off from the glass plate in cold water.

[0040] Example 4 S1. 1 g of fluorinated graphene was dispersed in 200 mL of N-methyl-2-pyrrolidone, and the mixture was heated under reflux at 80°C for 2.5 h. After cooling to room temperature, the mixture was sonicated for 4 hours to obtain a mixed solution of fluorinated graphene and N-methyl-2-pyrrolidone. The resulting dispersion was then centrifuged at 1000 rpm for 10 min to obtain the upper dispersion to remove unintercalated fluorinated graphene. The upper dispersion was centrifuged at 8000 rpm for 10 min to obtain the lower layer containing precipitate. The precipitate was obtained by vacuum filtration, washed three times with deionized water, and then vacuum dried at 50°C for 24 h. The dried solid was ground to obtain fluorinated graphene powder. The atomic ratio of fluorine to carbon in the sample was determined by X-ray energy dispersive spectroscopy to be 0.57, and the sample was designated as FG-0.57.

[0041] S2. Polyimide / fluorinated graphene composite films were prepared by in-situ polymerization. First, 0.028 g of FG-0.57 was added to 35 ml of N,N-dimethylacetamide solution and sonicated for 5 minutes. Then, 3.065 g of 4,4-diaminodiphenyl ether was added to the mixture, and the composite solution was heated and stirred in a 40°C constant temperature water bath for 1 hour at a speed of 200 r / min. After 4,4-diaminodiphenyl ether was completely dissolved, the water bath temperature of the composite solution was adjusted to 4℃. Then, 3.348g of pyromellitic dianhydride was added to the composite solution in three portions: 2g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 1.011g of pyromellitic dianhydride was added and stirred for 30 minutes at 200 rpm; 0.337g of pyromellitic dianhydride was added and stirred for 30 minutes, adjusting the stirring speed to 100 rpm to reduce bubble formation. The composite solution was stirred for 30 minutes to ensure sufficient reaction. Then, 0.045g of pyromellitic dianhydride was added and stirred for 1 hour at 100 rpm. Stirring was stopped after the solution exhibited a "climbing" phenomenon, yielding a polyamic acid / FG-0.57 composite solution. The solution was then degassed under vacuum to remove air bubbles, and the polyamic acid / FG-0.57 composite solution was coated onto a clean glass plate using a solution casting method. The glass plate was placed in a vacuum drying oven at 60°C for 2 hours, followed by a gradient heating process: 120°C for 30 min, 200°C for 30 min, 250°C for 30 min, and 300°C for 30 min. After the glass plate cooled to room temperature, the polyimide / FG-0.57 composite film was peeled off from the glass plate in cold water.

[0042] The breakdown field strength of pure polyimide films and polyimide-fluorinated graphene composite films prepared in four embodiments was tested, such as... Figure 5 As shown. The thermal conductivity of the pure polyimide film and the polyimide-fluorinated graphene composite film prepared in the four examples was tested, as shown. Figure 6 As shown. The thermogravimetric curves of pure polyimide films and polyimide-fluorinated graphene composite films prepared in the four examples are shown. Figure 7 As shown. The stress-strain curves of pure polyimide films and polyimide-fluorinated graphene composite films prepared in the four examples are shown below. Figure 8 As shown, the composite film exhibits superior electrical insulation, thermal stability, and mechanical properties compared to pure polyimide film.

[0043] Table 1 compares the dielectric constants of the composite films of the prior art and the present invention. As shown in Table 1, in the prior art, the dielectric constant of the polyimide-based composite film gradually increases or decreases as the proportion of doped filler gradually increases, exhibiting a monotonic trend. However, the present invention achieves bidirectional control of the dielectric constant of the polyimide-based composite film by doping with the same type and proportion of filler (0.5 wt% FG), which is beneficial to improving the dielectric constant matching degree of interlayer insulating materials and improving the electric field distribution.

[0044] Table 1. Comparison of dielectric constants of composite films of the prior art and the present invention. like Figure 3 As shown, the pure polyimide film has a regular cross-section, while the micropores in the cross-section of the polyimide / fluorinated graphene composite film gradually decrease as the fluorine-carbon ratio of the fluorinated graphene decreases.

[0045] like Figure 4 As shown, by adjusting the fluorine-carbon ratio of fluorinated graphene, the dielectric constant of the composite film can be controlled within the range of 3.0-5.9 with 4.0 as the center, provided that only 0.5wt% fluorinated graphene is doped.

[0046] To verify the stability of the electrical, thermal, and mechanical properties of the composite film, the breakdown field strength, thermal conductivity, thermogravimetric curves, and stress-strain curves of the pure polyimide film and the polyimide / fluorinated graphene composite film prepared in four examples were tested. Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown, the composite film exhibits superior electrical insulation, thermal stability, and mechanical properties compared to pure polyimide film.

Claims

1. A method for preparing a polyimide-fluorinated graphene composite film with bidirectionally tunable dielectric constant, characterized in that, Includes the following steps: S1. Fluorinated graphite is exfoliated into fluorinated graphene in N-methyl-2-pyrrolidone solution by ultrasonic-assisted solvothermal intercalation. The dispersion is then centrifuged once at low speed to obtain the upper dispersion, and then centrifuged once at high speed to obtain the precipitate solution. The precipitate solution is filtered, washed, dried and ground to obtain fluorinated graphene powder. S2. Composite solutions of fluorinated graphene and polyamic acid with different fluorine-to-carbon ratios were prepared by in-situ polymerization. The composite solutions were coated on a clean glass plate by solution casting and subjected to defoaming and thermal imidization reactions to obtain polyimide fluorinated graphene composite films.

2. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 1, characterized in that, The mass fraction of fluorinated graphene is 0.5 wt%.

3. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 2, characterized in that, To obtain fluorinated graphene with different fluorine-to-carbon ratios, the fluorine-to-carbon ratio of the fluorinated graphene was controlled by ultrasound, with the ultrasound time of the fluorinated graphene composite solution ranging from 4 to 128 hours.

4. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 3, characterized in that, To obtain fluorinated graphene with a fluorine-to-carbon ratio of 1, the ultrasonication time is preferably 3-6 hours.

5. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 3, characterized in that, To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.9, the ultrasonic time is preferably 12-18 hours.

6. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 3, characterized in that, To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.7, the preferred ultrasonic time is 28-36 hours.

7. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 3, characterized in that, To obtain fluorinated graphene with a fluorine-to-carbon ratio of 0.6, the ultrasonic time is preferably 100-140 h.

8. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 1, characterized in that, During the low-speed centrifugation of the fluorinated graphene dispersion, the rotation speed is 800-2000 rpm and the centrifugation time is 8-15 min.

9. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 8, characterized in that, During the low-speed centrifugation of the fluorinated graphene dispersion, the rotation speed is 1000-1500 rpm and the centrifugation time is 10-12 min.

10. The method for preparing a polyimide fluorinated graphene composite film with bidirectionally tunable dielectric constant according to claim 9, characterized in that, During the high-speed centrifugation of the fluorinated graphene dispersion, the rotation speed is 6000-10000 rpm and the centrifugation time is 8-15 min.

Citation Information

Patent Citations

  • High dielectric constant nano-perovskite CsPbX3 / polyimide composite film and its preparation method

    CN111925540B

  • A high thermal conductivity and low dielectric constant polyimide film and preparation method thereof

    CN116285347B

  • Low-dielectric-constant porous polyimide microsphere / polyimide composite film as well as preparation method and application thereof

    CN117487352A

  • High-entropy ceramic-polymer composite energy storage dielectric thin film material, preparation method and application

    CN119505308A